Development of Teaching Materials Based on Contextual Teaching Learning (CTL) in Physical Chemistry Courses - Mukhlishin, Hamdil (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to produce teaching materials for the Physical Chemistry course that are based on the Contextual Teaching and Learning (CTL) approach that is valid, practical and effective. This research is included in the type of development research that adopts the 4D Model, which has been modified by the researcher from four steps to three research steps. The analysis was carried out in two stages, namely problem analysis and needs analysis. The validity of teaching materials involves material experts, media experts and language experts. The practicality of teaching materials is assessed by filling out a questionnaire by users of teaching materials, namely lecturers and students. The product was tested on students of the Chemistry Education Study Program at Muhammadiyah University, Pontianak. Based on the analysis of student needs, it was found that students need learning resources for Physical Chemistry courses that are based on the Contextual Teaching and Learning (CTL) approach which can support skills in relating the material studied to everyday life. The techniques used are observation, interviews, validation questionnaires and student response questionnaires. The results obtained were that the validity of the material aspect was 98.75%, the media was 87.33%, and the language was 98.00%, which fell into very valid criteria. Practicality based on the student response questionnaire score in individual trials was 95.8% and in small group trials was 89.6%, which is very practical criteria. The effectiveness value obtained on average was 0.67 in individual trials which were in the high criteria and 0.82 in small group trials in the very high criteria.